The Batman [videorecording (DVD)] - Reeves, Matt, 1966-; Reeves, Matt, 1966-; Pattinson, Robert; Kravitz, Zoë; Wright, Jeffrey (Warner Bros. Entertainment, 2022)
Batman must investigate Gotham City's hidden political corruption when the Riddler begins murdering key political figures.